Strengthening fetal heart rate monitoring during labor with a standard handheld doppler - Implementation experience from India - Devina Bajpayee; Enisha Sarin; Sourav Ghosh Dastidar; Subodh Chandra; Jaya Swarup Mohanty; Nitin Bisht; Arvind Kumar; Harish Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: India's neonatal and perinatal mortality is among the highest in the world. Intrapartum-related conditions contribute to a significant proportion of neonatal deaths and stillbirths. Fetal heart rate monitoring, a recommended norm to assess fetal well-bring, is not practiced as per standard guidelines in public health facilities. A standardized Doppler along with training on fetal heart rate monitoring was implemented across different levels of healthcare in three states. Methods: Facilities were selected purposively to implement the Doppler. Baseline data for 3 months were collected. Interviews of health providers and observation of labor were conducted quarterly. Data were analyzed through a comparison of baseline and intervention on a number of delivery and monitoring indicators. Results: Among 22,579 total deliveries, monitoring frequency increased along with increase in detection of abnormal fetal heart rate (FHR) while cesarean section and stillbirths reduced slightly. Cases never monitored reduced in the District Hospitals (7.98-2.07, P < 0.01) and in Community Health Centers (14.7-1.67, P < 0.001). Stillbirth rate reduced at the medical college (3.6-1.1, P < 0.001). Interviews with providers revealed acceptance of the device due to its reliable readings. Conclusion: The Doppler demonstrates acceptability and serves as a useful aid to improve intrapartum FHR monitoring.